2014
DOI: 10.1098/rsbl.2014.0684
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetence and high metabolic rates enhance overwinter survival in the root vole, Microtus oeconomus

Abstract: Despite its presumed significance, the association between immune defence, energy expenditures and overwinter survival is rarely studied. We analysed individual variation in immunocompetence quantified as neutrophil-tolymphocyte ratio (N/L), total white blood cells (WBC) and natural antibody levels, along with resting (RMR) and peak metabolic rates (PMR) and mortality during three consecutive winter seasons in a natural population of the root vole, Microtus oeconomus. In early winter, WBC count was negatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Different immune components are not necessarily positively related to each other [41]. Although negative associations are consistent with a trade-off between different components of immunity [42], other studies detected positive or no associations among different lines of immunity [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different immune components are not necessarily positively related to each other [41]. Although negative associations are consistent with a trade-off between different components of immunity [42], other studies detected positive or no associations among different lines of immunity [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although selection acting on the immune system of birds at Chernobyl during the last 30 years may explain inconsistency of results and the absence of a relationship between different levels of radioactivity and innate immune response of individuals affected by the Chernobyl catastrophe, this could also be due to different aspects of immune responses being investigated in different studies. Different immune components are not necessarily positively related to each other [ 41 ]. Although negative associations are consistent with a trade-off between different components of immunity [ 42 ], other studies detected positive or no associations among different lines of immunity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, WBC was found the highest in winter and the upward trend was also obvious for the recovery of immunity in many other immunology findings, which are complied with similar phenomenon found previously in root voles. The rising number of WBC and other indexes would make them survive better in winter Zub, 2014;Książek andZub, 2017). For the reason of the primier rising of MCV in autumn might suggest the mechanism of resistance to the reduction of MCH and MCHC.…”
Section: Winter Immunity Recoverymentioning
confidence: 99%